Problematika Pendidikan Moral Di Sekolah Dan Upaya Pemecahannya - Nanang Abdillah (Program Studi Pendidikan Guru Madrasah Ibtidaiyah, 2020)
ABSTRACT School is an institution that tries to process input in the form of students into outputs that not only master knowledge from one domain, but from the three domains, namely cognitive, effective and psychomotor comprehensively including moral education. But in reality, it is often found deviations of student behavior, which in turn emerge moral degradation in students. Schools will have more meaning if they have implemented moral education in students in totality.